Diagnosis of pleural fluid effusions by cell block and pleural biopsy – A comparative study - S S Sabitha Rani; Immadi Sudhakar Vamshidhar; Nitin Ashok John; Jyoti John (Journal of Cytology, 2022)
Background: Cytological smear and cell block are commonly used to diagnose pleural fluid effusion. However, there is a paucity of information in the literature where a comparison between a cytological smear and a cell block with corresponding pleural biopsy has been done. This study aimed to evaluate the accuracy of cytological smears, cell blocks, and pleural biopsy for the diagnosis of malignant tumors. Material and Methods: In this cross-sectional study, analysis of successive pleural fluid samples received by the department was done. The sample was divided into equal halves of 5 ml each. One was used for conventional smear and the second was used for the preparation of cell block. The cell block was prepared by centrifuging the specimen of fluid at 2500 rpm for 15 min. A pleural biopsy was obtained by using Cope's pleural biopsy needle. Results: A total of n = 50 cases were included in the study. A total of n = 8 cases were diagnosed as malignant by cell smear and n = 4 cases were suspicious for malignancy. By cell block, n = 10 cases of malignancy were diagnosed and n = 1 case was suspicious for malignancy. By biopsy, n = 11 cases were diagnosed as malignant and n = 1 case was suspicious for malignancy. Out of the total, n = 2 cases were diagnosed as squamous cell carcinoma by biopsy; one case was diagnosed by cell block; and the other was reported as suspicious for malignancy. Conclusion: The study shows that cell blocks are complementary to the cell smear technique in over diagnosis and categorization of benign as well as malignant cells. The cell blocks were more useful in the diagnosis of malignancy because of better preserved architectural patterns as seen in corresponding histopathology sections. It, therefore, appears that the cell blocks are a perfect fit to bridge the cytology and histopathology.